2003
DOI: 10.3122/jabfm.16.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Mind-Body Medicine: State of the Science, Implications for Practice

Abstract: Background: Although emerging evidence during the past several decades suggests that psychosocial factors can directly influence both physiologic function and health outcomes, medicine had failed to move beyond the biomedical model, in part because of lack of exposure to the evidence base supporting the biopsychosocial model. The literature was reviewed to examine the efficacy of representative psychosocial-mind-body interventions, including relaxation, (cognitive) behavioral therapies, meditation, imagery, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
261
1
9

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 426 publications
(277 citation statements)
references
References 157 publications
6
261
1
9
Order By: Relevance
“…The boundaries between the different types of mind body therapies are not easily defined, and therapies are therefore often discussed collectively (Astin et al, 2003). Guided imagery is often used to aid hypnosis, or meditation, or combined with other techniques such as progressive muscle relaxation, but the technique can also be used alone.…”
Section: Introductionmentioning
confidence: 99%
“…The boundaries between the different types of mind body therapies are not easily defined, and therapies are therefore often discussed collectively (Astin et al, 2003). Guided imagery is often used to aid hypnosis, or meditation, or combined with other techniques such as progressive muscle relaxation, but the technique can also be used alone.…”
Section: Introductionmentioning
confidence: 99%
“…The other study on LBP showed no significant differences in pain reduction between patients who received breath therapy (i.e., integrated approach of body awareness, breathing, meditation, and movement) compared with physical therapy [87]. The single study on fibromyalgia compared MBSR and qigong with an education control group [78,88]. Nearly 50 percent of patients from both groups dropped out and no group differences in pain were found at any assessment point.…”
Section: Meditationmentioning
confidence: 99%
“…(32) The National Institutes of Health defines mind-body therapies as "interventions that use a variety of techniques designed to facilitate the mind's capacity to affect bodily function and symptoms." (33) In adults, significant benefits of Tai Chi, a Chinese mind-body practice that involves meditation, deep breathing, and slow, gentle movements, (34) have been demonstrated in individuals with fibromyalgia. A number of trials have assessed various forms of mindfulness meditation, with promising results in outcomes that range from pain to physical function to tender points.…”
Section: Mind-body Therapiesmentioning
confidence: 99%